FINISTERRA ANNUAL LECTURE: VALUING PLACE IN A CHICAGO MARKET - Cressweel, Tim (Finisterra, 2019)
This essay approaches the ideas of value and valuing though an exploration of the Maxwell Street market in Chicago, USA. The market was the largest open-air market in North America for much of the twentieth century. From the 1960s onwards it has been subjected to various forms of valuing and devaluing leading to its eventual demise in its historic location in 1994. The essay explores how the market and things in the market entered and left various regimes of value over time. The focus is on the role of hub-caps, home-made instruments called Stradizookys, and the process of tax-increment financing. The essay ends with some thought around order and regulation in the urban landscape.